Improvement of Moderately Loaded Transonic Axial Compressor Performance Using Low Porosity Bend Skewed Casing Treatment - Dilipkumar Bhanudasji Alone; S. Satish Kumar; Shobhavathy M. Thimmaiah; Janaki Rami Reddy Mudipalli; A. M. Pradeep; Srinivasan Ramamurthy; Venkat S. Iyengar (International Journal of Rotating Machinery)
This paper presents experimental results of a single stage transonic axial flow compressor coupled with low porosity bend skewed casing treatment. The casing treatment has a plenum chamber above the bend slots. The depth of the plenum chamber is varied to understand its impact on the performance of compressor stage. The performance of the compressor stage is evaluated for casing treatment and plenum chamber configurations at two axial locations of 20% and 40%. Experimental results reveal that the stall margin of the compressor stage increases with increase in the plenum chamber volume. Hot-wire measurements show significant reduction in the turbulence intensity with increase in the plenum chamber volume compared to that with the solid casing at the stall condition. At higher operating speeds of 80% and at 20% axial coverage, the stall margin of the compressor increases by 20% with half and full plenum depth. The improvement in the peak stage efficiency observed is 4.6% with half plenum configuration and 3.34% with the full plenum configuration. The maximum improvement in the stall margin of 29.16% is obtained at 50% operating speed with full plenum configurations at 40% axial coverage.